2005
DOI: 10.1038/sj.eye.6701934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blindness and low vision in an Italian population: a comparison with other European studies

Abstract: Aim The scientific literature contains recent data on the prevalence of blindness and low vision for a few European countries, but most of these studies have been focused exclusively on the elderly sector of the populations. The purpose of the present study was to provide age-specific estimates of the prevalence and causes of visual loss in an Italian population aged 40 years and over. Methods In total, 847 of the 1200 citizens 440 years of age (70.6%) in the island community of Ponza underwent complete standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 13 publications
2
41
0
5
Order By: Relevance
“…It was ranked as the first to third most frequent cause of blindness in 6 population surveys, [22][23][24][25][26][27] and it is the primary cause in approximately 7% of individuals with low vision or blindness in European populations 22,23 and in 12% to 27% of individuals in Asian populations. [25][26][27] Myopic macular degeneration accounts for up to 12.5% of visual impairment in the Shihpai study 28 and 22.4% in the Tajimi study, where it is the leading cause of monocular blindness and third leading cause of bilateral low vision.…”
Section: Pathologic Myopia Definitionmentioning
confidence: 99%
“…It was ranked as the first to third most frequent cause of blindness in 6 population surveys, [22][23][24][25][26][27] and it is the primary cause in approximately 7% of individuals with low vision or blindness in European populations 22,23 and in 12% to 27% of individuals in Asian populations. [25][26][27] Myopic macular degeneration accounts for up to 12.5% of visual impairment in the Shihpai study 28 and 22.4% in the Tajimi study, where it is the leading cause of monocular blindness and third leading cause of bilateral low vision.…”
Section: Pathologic Myopia Definitionmentioning
confidence: 99%
“…Betegeink azonban sok esetben csak késéssel kerülnek a megfelelő centrumba, ahol a szükséges kezelést megkaphatják, ez pedig szintén magyarázhatja a kisebb mértékű javulást. További ok lehet az első évi viszonylag alacsony átlag-injekciószám (1,8), amely kevesebb mind a REPAIR (3,6), mind a RADIANCE (4,6, illetve 3,5) tanulmányban egy év alatt adott kezelések számához képest. Más tanulmányokban a mi eredményeinkhez hasonló volt az egy év alatti visusjavulás mértéke [28,31].…”
Section: Eredeti Közleményunclassified
“…A chorioidealis neovascularisatio (CNV) gyakorisága patológiás myopiában 5,2-11,3%, és 15%-ban bilateralis [1]. Két európai tanulmány eredményei alapján a vakság, illetve gyengén látás 5,8, valamint 7,8%-áért a patológiás myopia tehető felelőssé [2,3]. Magyarországi adatok szerint a myopia a vakság negyedik leggyakoribb oka az időskori maculadegeneráció (AMD), a glaucoma és a diabeteses retinopathia után (két megye adatai alapján a vakság 10,8%-ért tehető felelőssé), fiatalabb korban ez az arány még magasabb (a 0-39 éves korcsoportban 21%, a 40-59 éves korcsoportban 14%) [4].…”
unclassified
“…[23][24][25] Visual acuity (VA), which is the specific focus of the present analysis, was evaluated separately for each eye with a standard 10-letter logarithmic chart at a distance of 4 m. 26 Near and distant VA was evaluated under uncorrected (VA UC ), presenting (VA PR ), ie with any corrective lenses (spectacles or contact lenses) being used by the subject (information elicited by specific questioning), and best-corrected (VA BC ) conditions. The latter evaluation was based on automated measurement of refraction and the results of trial correction using spherical and cylindrical lenses, the red-green duochrome test, and the dynamic crosscylinder test in natural accommodation.…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment methods used have been fully described elsewhere. [23][24][25] The study began in 1988, when standardized ophthalmologic examinations were offered to all legal residents of Ponza aged 40 years and over who actually lived in the community for at least 9 months of the year (eligible population). In the spring of 2000, a follow-up study was conducted to determine the incidence of VI; the results have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%